2013
DOI: 10.1016/j.conbuildmat.2013.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity quantification of jointed plain concrete pavement mechanistic-empirical performance predictions

Abstract: This paper focuses on quantitative and qualitative sensitivity analyses of various jointed plain concrete pavement ( JPCP) mechanistic-empirical design scenarios. Two base cases of JPCP types were utilized: (1) new construction on granular base (new JPCP case), and (2) both new construction/reconstruction on stabilized foundations or rehabilitation on underlying asphalt/concrete layers ( JPCP over stiff foundation case). Each base case was designed for three traffic levels in five climate zones to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…New flexible pavements and new JPCPs were analyzed. The pavement structures, traffic loads, material properties, and other inputs for the analysis corresponded to the medium traffic cases for the sensitivity analyses described in Schwartz et al (12) and Ceylan et al (13).…”
Section: Comparisons Of Predicted Pavement Performancementioning
confidence: 99%
See 1 more Smart Citation
“…New flexible pavements and new JPCPs were analyzed. The pavement structures, traffic loads, material properties, and other inputs for the analysis corresponded to the medium traffic cases for the sensitivity analyses described in Schwartz et al (12) and Ceylan et al (13).…”
Section: Comparisons Of Predicted Pavement Performancementioning
confidence: 99%
“…ated the sensitivity of MEPDG performance predictions to traffic, material, and other design input parameters, but few comprehensive sensitivity studies of the effects of climate on performance predictions have been performed (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Nearly all sensitivity analyses of MEPDG performance predictions to climate inputs to date have simply compared results using one weather station to results using another (15,16).…”
mentioning
confidence: 99%
“…The overall survey results suggest that the joint spacing input for rigid pavement design varied between 15 to 20 feet, a significant spread. Multiple studies have previously reported joint spacing to be one of the most sensitive inputs to predicted pavement distresses (Ceylan, et al, 2013b;, so additional analysis was performed in this study to determine the impact of joint spacing on thickness and achieved reliability. Three values of joint spacing (15, 17, and 20 feet) were considered.…”
Section: Effect Of Joint Spacing For Rigid Pavementsmentioning
confidence: 99%
“…Volume 5, 2024, Pages 840-848 Proceedings of 60th Annual Associated Schools of Construction International Conference most research revolved around the mechanical properties including compressive strength, elastic modulus, and modulus of rupture (MOR) and thermal properties including coefficient of thermal expansion (CTE) (Sabih 2016), (Vandenbossche 2011), (Ceylan 2013). There are a few works on the analysis of the effect of thermal stress and coefficient of thermal expansion on concrete pavements (Mackiewicz 2014), (Shin 2011) but not much research is available on the effects of thermal conductivity (TC) on the performance of the JPCP system (Mirnezami 2023), (Panchmatia 2014), (Kodide 2010), , (Cavalline and Morrison 2018).…”
Section: Epic Series In Built Environmentmentioning
confidence: 99%